Evaluation of the renal function in patients with nephrectomy - Tomás de Armas Gil; Lázaro L. Capote Pereira; Juan B. Castañer Moreno; Yeneisis Herrera Oropesa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: several studies have been published by different groups of work about the evaluation of the renal function in nephrectomized patients, showing varied results. In some cases it is reported the deterioration of the remaining kidney, and not in others. Objective: to describe the adaptative response regarding renal and clinical evolution in nephrectomized patients. Methods: cross study in which it was evaluated the renal function before and at two years of nephrectomy of 38 patients. The variables analyzed were glomerular filtration rate, creatinine and serum urea and associated diseases. Rates, percentages and Squared Chi for qualitative variables so as mean, standard deviation and Students T test for quantitative ones. Results: serum creatinine mean after nephrectomy was superior to the pre-nephrectomy (102 umol vs 126) p=0,05. Glomerular Filtration rate decreased after nephrectomy (62 ml/min vs 43 ml/min) p=0,02. Hypertensive and diabetic patients had a higher deterioration of the renal function, p≤0,05. Conclusion: nephrectomy produces a deterioration of the renal function at two years of follow up mainly in diabetic and hypertensive patients.